The Growth-Employment-Poverty Nexus in Latin America in the 2000s: Cross-Country Analysis - Cruces, Guillermo (2016)
In the great majority of Latin American countries in the 2000s, economic growth took place and brought about improvements in almost all labour market indicators and consequent reductions in poverty rates. Across countries, economic growth was not all that mattered; external factors were particularly important for changes in labour market conditions, while reductions in poverty were strongly related to improvements in earnings and employment indicators. Although the 2008 crisis affected some countries differently from others, nearly all labour market indicators were at least as high or higher by 2012 than immediately before the crisis in all countries but one.